Viruses of the family Bunyaviridae: are all available isolates reassortants? - Briese, Thomas; Calisher, Charles H.; Higgs, Stephen (My University, 2013)
Viruses of the family Bunyaviridae (the bunyaviruses) possess three distinct linear, single-stranded, negative sense or ambisense RNA segments (large, medium, and small). Dual infections of arthropod and perhaps vertebrate and plant hosts provide substantial opportunity for segment reassortment and an increasingly recognized number of the nearly 300 viruses in this family have been shown to be reassortants. Reassortment of RNA segments (genetic shift) complements genetic drift (accumulation of point mutations) as a powerful mechanism underlying bunyavirus evolution. Here we consider the possibility, if not likelihood, that most if not all bunyaviruses currently recognized may represent reassortants, some of which may be reassortants of existing viruses, and some of which may be reassortants of extinct viruses. If this hypothesis is correct, then the roots of the family and genus trees of bunyaviruses as currently described (or ignored) are incomplete or incorrect.
Keywords: Bunyaviridae; Bunyaviruses; Genome segment reassortment; Tripartite genome; Phylogenetics